Design and Development of a Vertical Axis Wind Turbine with PVC Blades Using Solidworks Simulation - Ramadan Bimo Anggoro; Ramadhani Setyobudi; Amajida Sadrina; Siti Chalimah; Muhammad Hendra Budi Satria (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2024)
Savonius wind turbines have better performance in locations with varying wind directions compared to horizontal axis wind turbines. However, their drawback lies in their low performance coefficient. The main objective of this study is to investigate the optimal design of a vertical axis wind turbine of the Savonius type. The parameters investigated include blade thickness and blade arc angle. This study was conducted using computational fluid dynamics (CFD) simulations with SolidWorks software. The simulation results show that at various blade thicknesses, there are significant differences in the obtained power coefficient () values. At a blade thickness of 2 mm, the highest power coefficient () reached 0.38 with a blade arc angle of 130º. Meanwhile, a blade thickness of 3 mm showed a maximum power coefficient () of 0.41 at a blade arc angle of 120º. However, at a thickness of 4 mm, there was a significant increase with the highest power coefficient () reaching 0.45 at a blade arc angle of 110º. This indicates that the most efficient shape for a Savonius wind turbine is with a blade thickness of 4 mm, a blade arc angle of 110º, a blade spacing of 3 cm, and an overlap ratio of 0.42, providing a maximum power coefficient () of 0.45.